Secondary prevention of cervical cancer: a modern approach to diagnosis - T. V. Klinyshkova (Лечащий Врач)
According to WHO, cervical cancer is the fourth most common type of cancer among women in the world, in 2020 the number of new cases of the disease reached 604,000. Among women of reproductive age, cervical cancer is the second most com[1]mon type of cancer and the second cause of cancer death in the world. In the Russian Federation, the incidence of cervical cancer in recent years has been in the second position after uterine body cancer in the structure of genital cancers in the country. The problem of increasing incidence of cervical cancer requires the improvement of cervical screening. The last decade is characterized by the emergence of new highly informative methods for diagnosing precancer and the active introduction of modern approaches into practice in many countries. In the WHO Global Strategy to Accelerate the Elimination of cervical cancer as a public health problem, cervical screening is given priority. Modern cervical screening includes switching to primary human papillomavirus (HPV) screening or a соtesting followed by a triage in case of human papillomavirus detection. An overview and analysis of current data on this problem over the past decade is presented. The issues of evidence of the informativeness of traditional cytological screening, liquid cytology, HPV screening, cotesting, triage strategies of HPV-positive women, human papillomavirus screening interval are discussed. The immunocytochemical method of double staining p16/Ki67 is proposed for triage HPV-positive women, as more informative than cytological for the detection of CIN2+/CIN3+, an assessment of the risk stratification of precancerous using this method was carried out. Along with the expansion of human papillomavirus vaccination, increasing the level of cervical screening and coverage of the female population will help to reduce the morbidity and mortality associated with cervical cancer.